Research on Prediction and Optimization Design Method of Slip Anchoring Performance Based on BP&NSGA-II - Ming, Lu; Hualin, Liao; Huajian, Wang; Jiansheng, Liu; Yuhang, He; Fengtao, Qu; Wenlong, Niu; Yifan, Wang (Frontiers in Energy Research, 2022)
The slip of the packer is the core part of the anchoring system. Unreasonable design of the slip structure can easily cause damage to the anchor claw of the slip, unstable anchoring, and even damage to the casing. At present, the main methods of slip anchoring performance tests are indoor design and field tests, and slips with different structural parameters need to be processed to verify their anchoring performance. In order to ensure that the slips can play a good anchoring effect and reduce the damage to the casing, this study uses a combination of finite element analysis, BP&NSGA-II, and indoor tests to study the mechanical behavior of the slips during the anchoring process. A prediction model was established to optimize the key parameters affecting anchoring performance, such as slip angle, inclination angle, inner cone angle, the radius of curvature, and spacing. Indoor experiments show that the prediction method can greatly improve the efficiency and accuracy of the design and test the anchoring performance of slips.